Case Report: Stable disease achieved in a patient with metastatic castration-resistant prostate cancer following personalized treatment - Zhang, Fan; Zhang, Li; Pang, Dongzi; Wei, Shuqing (Frontiers in Oncology, 2025)
Castration-resistant prostate cancer (CRPC), particularly metastatic castration-resistant prostate cancer (mCRPC), is a leading cause of cancer-related death in men worldwide. Despite great achievements in the treatment of mCRPC, the clinical treatment still faces enormous challenges due to natural or acquired drug resistance. Tumor organoids, an in-vitro three-dimensional microstructure, have been demonstrated to predict the response to various therapies to optimize patient outcomes at the individual level. Here, we shared a mCRPC patient who achieved stable disease after treatment with the drugs sensitive in organoid drug screening, despite failure in previous several standard therapies. This typical case highlights that prostate cancer organoids may serve as a potential companion tool to optimize treatment options and improve treatment outcomes, thus realizing the personalized management of mCRPC patients, especially those exhausting the standard therapies.